2003
DOI: 10.1108/00346650310499730
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and constraints in the functional food market

Abstract: Reviews the main food choice trends driving consumer demand for functional foods and the constraints limiting market development. Considers previous research activity in the functional food arena and subsequently identifies paramount research priorities that may facilitate the development of products that will help satisfy consumer demands for convenience, health and sensory pleasure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 10 publications
0
44
0
1
Order By: Relevance
“…Bhaskaran and Hardley (2002) concluded that taste, quality, price/value, convenience and the health effects of functional foods are the key factors in purchase intention. Also, Gray, Armstrong, and Farley (2003) observed that functional foods have to answer the consumersÕ needs for convenience, health and good taste. Verbeke (in press) state that consumers are not ready to compromise on the taste of functional foods for health and thus, the health benefits do not allow any trade-off with taste.…”
Section: Functional Food Marketsmentioning
confidence: 98%
“…Bhaskaran and Hardley (2002) concluded that taste, quality, price/value, convenience and the health effects of functional foods are the key factors in purchase intention. Also, Gray, Armstrong, and Farley (2003) observed that functional foods have to answer the consumersÕ needs for convenience, health and good taste. Verbeke (in press) state that consumers are not ready to compromise on the taste of functional foods for health and thus, the health benefits do not allow any trade-off with taste.…”
Section: Functional Food Marketsmentioning
confidence: 98%
“…The market of functional food products is growing constantly and the future of functional foods looks quite optimistic (Gray, Armstrong, & Farley, 2003). The development and marketing the functional foods can be, however, very challenging compared to the foods that conventionally have a high health image.…”
Section: Introductionmentioning
confidence: 99%
“…Energy bars, a food product that fits these criteria, continue to increase in sales according to the ACNielsen Market Track (Burn 2007). Due to growing consumer demand for healthy, natural and convenient foods, attempts are being made for dehulling of flaxseed (Barnwal et al 2010;Oomah and Mazza, 1998;Zhang et al 2009) to improve the nutritional value of snack foods by modifying their nutritive composition (Bhaskaran and Hardley 2002;Gray et al 2003).…”
mentioning
confidence: 99%